2022
DOI: 10.1038/s41419-022-05447-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a group of bisbenzylisoquinoline (BBIQ) compounds as ferroptosis inhibitors

Abstract: Ferroptosis induced by detrimental accumulation of lipid peroxides has been recently linked to a variety of pathological conditions ranging from acute tissue injuries to chronic degenerative diseases and suppression of ferroptosis by small chemical inhibitors is beneficial to the prevention and treatment of these diseases. However, in vivo applicable small chemical ferroptosis inhibitors are limited currently. In this study, we screened an alkaloid natural compound library for compounds that can inhibit RSL3-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…We noticed that five of them (berbamine, cepharanthine, fangchinoline, liensinine and isoliensinine) belong to the bisbenzylisoquinoline (BBIQ) compounds that we recently identified as RTAs and ferroptosis inhibitors [ 44 ]. Consistent with our previous studies, we found these BBIQ compounds effectively block RSL3-induced ferroptosis in HT1080 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We noticed that five of them (berbamine, cepharanthine, fangchinoline, liensinine and isoliensinine) belong to the bisbenzylisoquinoline (BBIQ) compounds that we recently identified as RTAs and ferroptosis inhibitors [ 44 ]. Consistent with our previous studies, we found these BBIQ compounds effectively block RSL3-induced ferroptosis in HT1080 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified nine otoprotective compounds from this screen and two of them function to block neomycin uptake and seven of them inhibit ferroptosis, supporting an otoprotective function upon ferroptosis inhibition. Among the seven ferroptosis inhibiting compounds, berbamine, cepharanthine, fangchinoline, liensinine and isoliensinine are BBIQ compounds that were recently identified as ferroptosis inhibitors in our cell-based screen [ 44 ]. Catharanthine does not contain the chemical backbone of BBIQ compounds, but it also has ROS scavenging activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Ferroptosis inhibitors, primarily radical-trapping antioxidants and iron chelators, aim to mitigate OS and safeguard cells. 12,13 However, there are signicant hurdles in the initial generation of these compounds in clinical advancement due to off-target effects, limited selectivity, and potential toxicity. 14 Iron chelators, such as deferoxamine, are hindered by poor absorption and rapid clearance.…”
Section: Introductionmentioning
confidence: 99%